The potential reproductive contribution of Mediterranean migrating eels to the Anguilla anguilla stock - Capoccioni, Fabrizio (Sci Rep, 2014)
The European eel is a highly migratory fish. After the reproduction in the Sargasso Sea early larval-stages start a passive ocean migration towards European and Mediterranean continental waters. After several years as yellow eels, mature adults change to silver stage and then start their return trip. The trajectory of their backward migration is unknown, because of low probability of capturing migrating individuals, having this capture never been reported in the Mediterranean. Recently, 8 silver eels were collected in the Strait of Sicily. Using literature information about possible individual route and speed, their geographical position was projected up to the spawning site during reproductive season. Despite using optimal and continuous migration swimming speed, none of the specimens may have been able to reach the Sargasso Sea in time for mating. Subsequently, to identify putative Mediterranean areas from which eels could have been reaching the spawning grounds on time, a backward scenario was postulated using the previous scientific assumptions. Our results suggests that just a small quota of Mediterranean silver males successfully reaches the Sargasso area, and only females from the westernmost and central parts of the basin could be able to fruitfully pond their eggs during the supposed spawning period.